Tunisian-Maghreb relations and Habib Bourguiba’s position on the unity of the Arab Maghreb "1957-1987" - abbou, nadjet (The Algerian Historical Journal, 2026)
In this article, we will discuss a brief study of the nature of Tunisian-Maghreb relations during the era of President Habib Bourguiba, through our discussion of Tunisia’s position on Maghreb unity, especially since President Bourguiba was known for his Qatari tendencies. Then we touched on the course of relations between Tunisia and neighboring countries, which were known to deteriorate due to the borders. We also provided a summary of Tunisian-Moroccan relations, and Bourguiba’s position on the Western Sahara issue